Challenges and advances in the right to independent living. Accessibility, deinstitutionalisation and personal assistance in the Spanish context - Serra, María Laura; Poyatos Pérez, Rocío (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
This article provides a detailed analysis of the Spanish context in relation to the independent living of people with disabilities. It emphasises the importance of accessibility, deinstitutionalisation, and personal assistance as key factors. Four years after Spain’s review by the Committee on the Rights of Persons with Disabilities, a thorough examination of the policies and laws implemented by the Spanish government is conducted from a human rights perspective. The article updates and delves into the debates on achieving independent and autonomous living for people with disabilities in Spain, offering a comprehensive view of the legal and political environment that facilitates this essential transformation.
Keywords: independent living; accessibility; personal assistance; deinstitutionalization